Design of a Partial Resonant Inverter for solar photovoltaic applications. (2nd October 2021) - Vidhya, C; Muralidharan, S; Ravikumar, V
Abstract : This paper presents a solar-powered Partial Resonant Inverter (PRI) interfaced with an asymmetrical cascaded nine-level inverter. The DC input of the proposed system is obtained using Solar Photovoltaic (SPV) panel. The input DC sources fed to the asymmetrical cascaded nine-level inverter are in the ratio of 1:3. The step modulated nine-level inverter works with a precalculated switching angle for a fixed modulation of 0.7. Compared to the conventional 50 Hz inverter and the multi-output transformer design, the proposed system is more compact because of the high-frequency AC link. The PRI ensures Zero Voltage Switching (ZVS) and reduces the switching losses. The proposed scheme has been validated in the MATLAB/ SIMULINK environment and an experimental prototype is built in the laboratory. Based on the investigations the Selective Harmonic Elimination (SHE) method gives superior performance when compared to the Optimal Harmonic Stepped Modulation (OHSM) method. From the results and comparative analysis, the proposed system uses fewer switches to obtain the nine-level output, uses the PRI setup with the multioutput transformer to make the design compact and improves the power quality of the system.